2019
DOI: 10.1016/j.redox.2019.101190
|View full text |Cite
|
Sign up to set email alerts
|

S-nitrosothiols and H2S donors: Potential chemo-therapeutic agents in cancer

Abstract: Nitric Oxide (NO) and Hydrogen Sulfide (H2S) are components of an “interactome”, which is defined as a redox system involving the interactions of RSS, RNS and ROS. Chemical interaction by these species is common and is characterized by one and two electron oxidation, nitrosylation, nitration and sulfuration/polysulfidation reactions. NO and H2S are gases that penetrate cell membranes, are synthesized by specific enzymes, are ubiquitous, regulate protein activities through post-translational modifications and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…It is noteworthy that either stable NRF2 knockdown or glutaminolysis inhibition with CB-839 markedly enhanced the sensitivity of PDAC cells to gemcitabine, and the anticancer effect was further potentiated when CB839 was used in combination with gemcitabine in in vivo experiments [115]. Taken together, these data have indicated that NRF2 actively participates in the regulation of glutamine metabolism in malignant tumors suggesting that alterations in the KEAP1/NRF2 signaling alone or in combination with concomitant oncogenic activation might uncover specific metabolic vulnerabilities that might be therapeutically targeted to treat otherwise resistant tumors [116].…”
Section: Nrf2 Controls Xct Antiport To Support Cell Survival Leading To Metabolic Addictionmentioning
confidence: 94%
“…It is noteworthy that either stable NRF2 knockdown or glutaminolysis inhibition with CB-839 markedly enhanced the sensitivity of PDAC cells to gemcitabine, and the anticancer effect was further potentiated when CB839 was used in combination with gemcitabine in in vivo experiments [115]. Taken together, these data have indicated that NRF2 actively participates in the regulation of glutamine metabolism in malignant tumors suggesting that alterations in the KEAP1/NRF2 signaling alone or in combination with concomitant oncogenic activation might uncover specific metabolic vulnerabilities that might be therapeutically targeted to treat otherwise resistant tumors [116].…”
Section: Nrf2 Controls Xct Antiport To Support Cell Survival Leading To Metabolic Addictionmentioning
confidence: 94%
“…), exogenously administered H 2 S donors reach high local concentrations, which are cytotoxic to cancer cells (but also to any other cell type) ( Figure 2 ). The various chemical classes of anticancer H 2 S donors, their cellular actions (which, in some cases include the initiation of mitochondrial cell death pathways), and the potential difficulties with testing and developing such compounds (e.g., the theoretical and practical problems around selective targeting of the tumor cells with H 2 S donors in vivo) are extensively discussed in specialized reviews [ 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ] and will not be reiterated in the current article.…”
Section: Anticancer Effects Of Pharmacological H 2 mentioning
confidence: 99%
“…To date, numerous H 2 S releasing drugs with different properties, donating mechanisms, and capabilities have been synthesized for experimental use. With the exception of their molecular targets, the anti-cancer effects of H 2 S donors have been extensively reviewed [26][27][28][29]. Herein, we will summarize recent findings on the roles of H 2 S donors in cancer management by illuminating their molecular targets, mechanisms involved and their downstream effects in cellular activities.…”
Section: Ivyspring International Publishermentioning
confidence: 99%